The Role of Artificial Intelligence (AI) in Enhancing Circular Economy and Strategic Green Marketing for Environmental Performance: A Mixed-Method Study - Keskin, Halit; Akgun, Ali E.; Esen, Emel (WILEY, 2025)
As environmental urgency and digital transformation converge, understanding how emerging technologies create sustainable value has become a strategic imperative for businesses. This study investigates how artificial intelligence (AI) enables circular economy (CE) practices and strategic green marketing orientation (SGMO) to improve environmental performance (EP). Anchored in the resource orchestration view (ROV) and supported by the dynamic capability view (DCV) and complementarity theory, the research highlights AI not only as a technological asset but as an orchestrated capability that complements circular and green strategic initiatives. A sequential mixed-method design was employed: a model developed from an extensive literature review was tested using survey data from 310 participants in 115 firms, and a qualitative content analysis of integrated corporate reports provided contextual validation. The model captures the relationships among AI usage, CE capacity, SGMO, and EP, and PLS-SEM was used to assess mediation (SGMO) and moderation (AI) effects. Findings reveal that CE capacity enhances EP directly and through SGMO, while strategically orchestrated AI strengthens these effects. The study contributes to theory by integrating ROV, DCV, and complementarity theory to explain how digital transformation and environmental strategies jointly create long-term environmental values.
Keywords: artificial intelligence; circular economy; environmental performance; mixed-method research; strategic green marketing orientation; SUPPLY CHAIN MANAGEMENT; BUSINESS MODEL; INSTITUTIONAL PRESSURES; RESOURCE ORCHESTRATION; COMPETITIVE ADVANTAGE; OPERATIONAL PRACTICES; DYNAMIC CAPABILITIES; INDUSTRY; FIRM; SUSTAINABILITY; Business & Economics; Environmental Sciences & Ecology